Molecular characterization of fowl adenoviruses isolated from inclusion body hepatitis outbreaks in commercial broiler chickens in Malaysia - M. A., Juliana; Mat Isa, Nurulfiza; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini (Universiti Putra Malaysia Press, 2014)
Fowl adenoviruses (FAdVs), belonging to the Aviadenovirus genus of the family Adenoviridae, have been classified into five species (A to E) and further divided into 12 serotypes. The objective of this study was to identify the serotype classification of five Malaysian FAdV isolates obtained from field outbreaks of IBH in commercial broiler chickens. Hexon-based polymerase chain reactions (PCR), combined with restriction enzyme analysis (REA), were applied. Viral DNA reacted positively with H1/H2 and H3/ H4 primer pairs which hybridised to highly conserved regions of the hexon genes. The restriction enzyme profiles of the H1/H2 fragment digested with HaeII and the H3/H4 fragment digested with HpaII revealed that all five isolates shared identical patterns and are characterised as being FAdV-8b, species E. Meanwhile, sequence analysis of the L1 loop region of the hexon gene revealed 98.1% identity with FAdV-8b strain 764. High bootstrap values in phylogenetic analysis supported the clustering of the Malaysian FAdV isolates into FAdV species E. The present study has provided a very useful reference for further studies of FAdVs in Malaysia. Vaccination strategies should be developed against FAdVs infection in commercial broiler chickens to prevent IBH outbreaks in the country.